2019
DOI: 10.17586/2220-8054-2019-10-4-466-474
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical cell performance Cu doped ZnO photoanode sensitized by xanthene dyes

Abstract: In this study transition metal Cu is doped into ZnO framework at 1, 3 and 5 mol% concentrations by sol-gel method and Photoelectrochemical performance under sensitization is recorded. Structural analysis XRD and Raman gives information of wurtzite structure formation without any mislaid peaks. It also informs decrement in crystalline size and lattice parameters as doping level increases. SEM and EDAX provide nono structure formation with appropriate compositions. Optical analysis by FTIR and PL gives peaks at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In 2014, Kanmani et al 48 found that 1%Ti doped ZnO based DSSC has maximum efficiency value about 0.19% by simple chemical method. In 2019, Kumbhar et al 49 described that DSSC has maximum efficiency about 0.1156% for 1% Cu doped ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Kanmani et al 48 found that 1%Ti doped ZnO based DSSC has maximum efficiency value about 0.19% by simple chemical method. In 2019, Kumbhar et al 49 described that DSSC has maximum efficiency about 0.1156% for 1% Cu doped ZnO.…”
Section: Introductionmentioning
confidence: 99%